Denominaciones de origen y conocimientos tradicionales: estudio comparado de legislación en América Latina. - Verdezoto Carvajal Anderson Miguel (2024)
The research presented constitutes a comparative study of legislation for the protection of traditional knowledge through regulations on apellations of origin of industrial property in Latin America. For this, the laws of Peru, Colombia, Venezuela and Panama have been taken as a reference in comparison with the Ecuadorian law. It is an issue that is currently being analyzed by the World Intellectual Property Organization (WIPO) with the idea of establishing a system of international protection that meets the expectations of indigenous and traditional communities around the world. Ecuador is part of this organization, as well as the rest of the Latin American countries, so its experience and needs deserve to be known, systematized and attended to. The aim is to contribute to this with this study that seeks to analyze the topic and systematize its theoretical and normative references in the area. The research carried out is of a legal dogmatic type with a qualitative approach. Combined methods of Social Sciences and Legal Sciences are used, such as analysis-synthesis, logical history, analytical exegesis and comparative law. The technique used to achieve the development of the research is bibliographic review. As expected results, the aim is to obtain a technical legal study that assesses the protection of traditional knowledge through appellations of origin in the comparative law of Latin America (Peru, Colombia, Venezuela and Panama) and, in particular, in the Republic of Ecuador, in its contribution to the theoretical and normative configuration Keywords: appellations of origin, traditional knowledge, comparative law, industrial property.